STRUKTUR AJARAN PENDIDIKAN KARAKTER DALAM GEGURITAN BUDI PEKERTI - Dyatmika, I Kadek Wahyu; Sutriyanti, Ni Komang; Widiantana, I Kadek (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2024)
Character education when viewed in the context of education in Indonesia refers to 18 noble values originating from the nation's culture and o foster the personality of the next generation (the younger generation). The teachings of character education can not only be found through learning in schools but can be seen in geguritan literary works. Geguritan Budi Pekerti is one of Bali Purwa's literary works which contains ethical and Hindu religious values. The problem that is studied in this scientific article is the structure of the teaching of character education in ethical behavior. The theory used in this study is Hans Georg Gadamer's Hermeneutical Theory which is strongly related to the interpretation of literary works and Charles Sanders Pierce's Semiotic Theory to study the doctrinal structure (icon) in Geguritan Budi Pekerti. This research is a qualitative research conducted by data collection methods through interviews, documentation, and literature study. The collected data were analyzed using the hermeneutic data analysis method and presented using inductive deductive techniques. The results of this study are in the form of a structure of character education teachings in Geguritan Budi Pekerti that is religious teachings, tolerance, honesty and social care.